The Effectiveness of Video Modelling to Teach Hotel Housekeeping Skills to Individuals with Intellectual Disabilities - Arzu Özen; H. Deniz Değirmenci (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Özel Eğitim Dergisi)
The aim of this study was to evaluate the effectiveness of video modelling in teaching hotel house-keeping skillsto adults with intellectual disabilities and to assess the acquisition of video-based non-target information. Amultiple probe across behaviours design was used. 4 adults with intellectual disabilities participated in the study.Baseline, probe, intervention, maintenance and generalization sessions were conducted. Results indicated thatvideo modelling was effective in teaching hotel house-keeping skills to adults with intellectual disabilities.Moreover, the acquired hotel house-keeping skills were maintained over time and generalized across settings andmaterials. The assessment of video based non-target skills data showed that participants acquired the non-targetinformation with the range from 33% to 100%. In conclusion video modelling can be used effectively in teachingvocational skills to adults with intellectual disabilities.